System of Carbon Dioxide (Co2) Detection Using Sim7600 Communication Module in Palm Oil Plantations - Febrin Aulia Batubara; Bakti Viyata Sundawa; Tuti Adi Tama Nasution (International Journal of Research in Vocational Studies (IJRVOCAS), 2023)
The problem of environmental damage caused by the palm oil industry has become a global issue. This often becomes an obstacle to the development of the palm oil industry in Indonesia. In fact, millions of Indonesians work in the palm oil sector and are a source of non-oil and gas state revenue. For this reason, efforts to support a sustainable palm oil industry need to be carried out. One of them is the implementation of a smart system in the form of a carbon dioxide (CO2) level detection system. It is important to know these parameters because they are affected by the expansion of oil palm plantations. The measurement results can be accessed and displayed in real-time web-based using the SIM7600 communication module. It is hoped that this CO2 detector will be a solution to environmental problems and related parties can determine mitigation actions in the most extreme conditions.